An ethnobotanical study of commonly growing weeds in wheat fields of District Chitral Lower, Pakistan: Ethnobotany of weeds - Sahar, Hasin; Ali, Fayaz (Ethnobotany Research and Applications, 2024)
Background: Native people of Chitral, located in the North of Pakistan, largely depends on food plants for medicines and other livelihood. The current study intended to document weed plant species frequently found in wheat fields and used by local community in traditional ways as food and ethno-medicines. Methods: An open ended and semi-structured questionnaire, group interviews and discussions were conducted from April 2022 to September 2023. A total of 153 local participants were interviewed for gathering information’s on the traditional uses of weeds species from wheat fields. Ethnobotanical data were analyzed using quantitative indices i.e. Use Value (UV), Informant Agreement Ratio (IAR), Relative Frequency of Citation (RFC). Results: We reported a total of 75 weed species belonging to 58 genera and 29 families, commonly consumed by the local communities. Floristic composition reveals Asteraceae as the dominant family having contribution of 14 species to the total, followed by family Lamiaceae (8 plant species) and Solanaceae. Interestingly, all the reported weed species in the wheat field were herbs. Leaf was the most consuming part of the reported weeds followed by flowers. Similarly, 25 plant species was used in making herbal tea. According to use value, Cichorium intybus L. was ranked on top having use value of 0.8 followed by Carum carvi and others. Conclusions: We concluded that wheat fields provide habitat to several important weed plant species. These important plant species may serve to guide developmental initiatives aimed at sustainable and culturally local projects. The results emphasizing the need for phytochemical studies to further validate their efficacy Keywords: Ethnobotany; Weeds; Medicinal uses; Chitral, Quantitative indices